RETRACTED: Olanzapine-Induced Activation of Hypothalamic Astrocytes and Toll-Like Receptor-4 Signaling via Endoplasmic Reticulum Stress Were Related to Olanzapine-Induced Weight Gain - He, Meng; Qian, Kun; Zhang, Ying; Huang, Xu-Feng; Deng, Chao; Zhang, Baohua; Gao, Guanbin; Li, Jing; Xie, Hao; Sun, Taolei (Frontiers in Neuroscience, 2021)
The antipsychotic drug olanzapine is associated with serious obesity side effects. Hypothalamic astrocytes and associated toll-like receptor-4 (TLR4) signaling play an essential role in obesity pathogenesis. This study investigated the effect of olanzapine on the astrocytes and TLR4 signaling both in vitro and in the rat hypothalamus, and their potential role in olanzapine-induced weight gain. We found that olanzapine treatment for 24 h dose-dependently increased cell viability, increased the protein expression of astrocyte markers including glial fibrillary acidic protein (GFAP) and calcium binding protein (S100B), and activated TLR4 signaling in vitro. In rats, 8- and 36-day olanzapine treatment caused weight gain accompanied by increased GFAP and S100B protein expression and activated TLR4 signaling in the hypothalamus. These effects still existed in pair-fed rats suggested that these effects were not secondary effects of olanzapine-induced hyperphagia. Moreover, treatment with an endoplasmic reticulum (ER) stress inhibitor, 4-phenylbutyrate, inhibited olanzapine-induced weight gain and ameliorated olanzapine-induced changes in hypothalamic GFAP, S100B and TLR4 signaling. The expression of GFAP, S100B and TLR4 correlated with food intake and weight gain. These findings suggested that olanzapine-induced, increased hypothalamic astrocytes and activation of TLR4 signaling were related to ER stress, and these effects may be related to olanzapine-induced obesity.